Secure distributed source coding with side-information - Luh, W.; Kundur, D. (IEEE communications letters, 2008)
This letter develops codes for the scenario in which users with correlated messages are to encipher and compress their messages without collaboration and without the use of cryptographic keys or other secret materials. We consider an eavesdropper that has access to an encoded message and in addition, some side-information in the form of uncoded symbols corresponding to the encoded message. Our codes are an extension of distributed source coding using syndromes (DISCUS) with the additional requirement of providing secrecy for the scenario described above. We state a secrecy condition that the subcodes of DISCUS must satisfy, and develop a general encoding algorithm meeting these conditions. We analyze the performance of the proposed code for the case of multiple eavesdropped messages.